Extracellular xylanase production by Pleurotus species on lignocellulosic wastes under in vivo condition using novel pretreatment - Singh, M. P.; Pandey, A. K.; Vishwakarma, S. K.; Srivastava, A. K.; Pandey, V. K. (Cellular and Molecular Biology, 2012)
The production of extracellular xylanase by three species of Pleurotus species i.e. P. florida, P. flabellatus and P. sajor caju was studied under in vivo condition during their cultivation on pretreated lignocellulosic wastes. Neem (Azadirachta indica) oil and ashoka (Saraca indica) leaves extract were used for pretreatment of paddy straw and wheat straw. Between these two wastes, paddy straw pretreated with neem oil, supported better xylanase production than wheat straw. Initially, xylanase production was low but it increased in subsequent days and reached at peak on 25th day of cultivation of Pleurotus species. Thereafter, there was decrease in the activity of the enzyme. On 25th day of incubation P. florida produced maximum xylanase on neem oil pretreated paddy straw i.e. 10.59 Uh-1ml-1. Among the three species, P. florida showed maximum enzyme activity followed by P. flabellatus and P. sajor caju.